The Influence of Tax Policy to Income Distribution: Indonesia Case - Mochamad Muslih; Dominik Tulasi; Soleha Soleha; Martina Uli Uli Silalahi; Gianti Putri Satgas Wali (JURNAL KEWIRAUSAHAAN, AKUNTANSI DAN MANAJEMEN TRI BISNIS, 2022)
One of the objectives of regulating taxation in Indonesia is to regulate the Indonesian economy. One of the taxation instruments used to drive the Indonesian economy is income tax. The purpose of this study is to study the effect of tax arrangements in Indonesia on the performance of the Indonesian economy. The method used is a quantitative method. The population is taxpayers in Indonesia. The selection of sample areas is carried out randomly. A total of 5 (five) cities in Indonesia were selected as samples. The results showed that taxation policies in Indonesia have not yet encouraged the distribution of public income